- #1

- 61

- 0

## Homework Statement

A mass [itex]m[/itex] rests on a frictionless horizontal table and is connected to rigid supports via two identical springs each of relaxed length [itex]l_{0}[/itex] and spring constant [itex]k[/itex].

*Each spring is stretched to a length [itex]l[/itex] considerably greater than [itex]l_{0}[/itex]*. Horizontal displacements of [itex]m[/itex] from its equilibrium position are labeled [itex]x[/itex] (along AB) and [itex]y[/itex] (perpendicular to AB).

*see attached image or link*

(a) Write down the differential equiation of motion (i.e., Newton's law) governing small oscillations in the [itex]x[/itex] direction.

(b) Write down the differential equiation of motion governing small oscillations in the [itex]y[/itex] direction (assume [itex]y[/itex]<<[itex]l[/itex]).

(c) In terms of [itex]l[/itex] and [itex]l_{0}[/itex], calculate the ratio of the

*periods*of oscillation along [itex]x[/itex] and [itex]y[/itex].

The rest of the question can be found on page 86 at http://www.scribd.com/doc/160672855/Vibrations-and-Waves-a-P-French

## Homework Equations

[tex]

F = ma \\

a^{2} + b^{2} = c^{2} \\

sin(\theta)≈tan(\theta) \text{ when } \theta \text{ is small} \\

(1+a)^{n} ≈ 1 + na \frac{n(n-1)a^{2}}{2!} +...\\

[/tex]

## The Attempt at a Solution

(a) I imagined a small displacement [itex]x[/itex] to the right, which I also declared to be positive.

[tex]

-k(l + x - l_{0}) + k(l-x-l_{0}) = ma \\

-2kx = ma \\

0 = ma + 2kx

[/tex]

(b) I tried going about this using some of the techniques discussed while doing question 3-7 which can be found here: https://www.physicsforums.com/showthread.php?t=694259 But my answer doesn't match the one in the back of the book and I'm not sure why.

I also imagined a small displacement [itex]y[/itex] so there is some force in each of the springs such that [itex]F_{L} = F_{R} = F[/itex], then the equation of motion in the [itex]y[/itex] direction looks like:

[tex]

2Fsin(\theta) = ma \\

sin(\theta) ≈ tan(\theta) = \frac{y}{l} \text{ *see attached attempt at inkscape*} \\

2F \frac{y}{l} = ma

[/tex]

[tex]

F = k(l'-l_{0}) \\

F = k\left(\left(y^{2}+l^{2}\right)^{\frac{1}{2}}-l_{0}\right)

[/tex]

[tex]

2k\left(\left(y^{2}+l^{2}\right)^{\frac{1}{2}}-l_{0}\right) \frac{y}{l} = ma\\

2k\left(l\left(1+\left(\frac{y}{l}\right)^{2}\right)^{\frac{1}{2}}-l_{0}\right) \frac{y}{l} = ma\\

\text{using the binomial approx...}\\

2k\left(l\left(1+\frac{1}{2}\left(\frac{y}{l}\right)^{2}\right)-l_{0}\right) \frac{y}{l} = ma\\

2k\left(y+\frac{y^{3}}{2l^{2}}-\frac{l_{0}}{l} y\right) = ma \\

\text{assuming y is small} \\

2k\left(1-\frac{l_{0}}{l}\right)y = ma \\

0 = ma + 2k\left(1-\frac{l_{0}}{l}\right)y

[/tex]

Also I see in the last step there is something going on with a sign, maybe it's because the way I set it up the displacement is in the negative direction.

(c)

[tex]

\omega_{x} = \left(\frac{2k}{m}\right)^{\frac{1}{2}}\\

\omega_{y} = \left(\frac{2k\left(1-\frac{l_{0}}{l}\right)}{m}\right)^{\frac{1}{2}}\\

\frac{T_{x}}{T_{y}} = \left(1-\frac{l_{0}}{l}\right)^{-\frac{1}{2}} \\

\text{The answer in the back of the book is:}\\

\frac{T_{x}}{T_{y}} = \left(1-\frac{l_{0}}{l}\right)^{\frac{1}{2}}

[/tex]